(untitled) (The Journal of Plant Protection Sciences, 2020)
Experiments were conducted at the Instructional Farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar during rabi season of 2002-03 and 2003-04 to study the population dynamics of mustard aphid on seven popular rapeseed-mustard cultivars. The incidence of aphid commenced from 52nd to 2nd standard week with a very low population levels on all the cultivars. The aphid (Lipaphis erysimi)population attained peak level from 7th to 9th standard week. The correlation coefficients between aphid population and different abiotic factors revealed contradictory results. Except for a few instances the weather parameters showed low order of associations with aphid population. Thus, the ecological factors exhibited little impact on the population build up of mustard aphid. The degree of infestation and the rates of population change of the aphids on different Brassica cultivars seem to be governed by varietal characteristics of different germplasms. Brassica campestris varieties as a group harbouredrelatively higher populations of the aphid than Brassica juncea varieties.